Bio-convective thermal melting applications of viscoelastic nanoparticles due to moving wedge - M. Ijaz Khan; Faris Alzahrani (Case Studies in Thermal Engineering, 2021)
The research communicates the melting applications of viscoelastic nanoparticles with microorganisms due to wedge-shaped configuration. The important features of activation energy, thermophoresis diffusion characteristics and Brownian motion are also highlighted. The analysis is performed in view of Melting process. The flow process is represented mathematically using partial differential equations. For the optimization technique using MATLAB computer-based tools, the Labotto IIIa formulation has utilized. In the velocity equation, the temperature profile, concentration profile and microorganisms' profile, the reporting of the main parameters are fully defined and discussed through figures. The speed can be enhanced by means of a mixed convection appearance is determined. Furthermore, nanoparticles are decreasing in temperature and concentration profiles and the high number of Peclet decreases the profile of microorganisms. This article's research includes a wide range of applications in nanotechnology, electrical and biomedical, biotechnology, medication delivery, chemotherapy, food processing, and other sectors. The claimed results reflect that increasing change in velocity is associated to the higher values of second grade fluid parameter and Marangoni ratio constant. The increase in wedge constant enhanced the velocity. Moreover, the concentration profile and microorganism field reduces with increasing Marangoni ratio constant.